A physical study of air–water flow in planar plunging water jet with large inflow distance. (March 2018) - Bertola, Numa; Wang, Hang; Chanson, Hubert
Highlights: Detailed measurement of air-water flow properties in supported plunging jets for a range of impact velocities; Detailed characterisation of inflow jet conditions with relatively high levels of jet disturbance and pre-aeration; Bubble-turbulence interplay characterised by bubble clustering properties and turbulent correlation time scales is under the impact of large jet disturbance; Advanced measurement and data processing techniques and large-size facility compared to literature; Significant contribution of jet pre-aeration to total air entrainment rate. Abstract: A plunging jet is commonly encountered in nature. It is also widely used in industry for its capacity to enhance fluid mixing and entrain gases into the liquid fluid when the impact velocity exceeds a critical value. This paper presents a physical study of vertical supported planar water plunging jets, in a relatively large-size facility. Air-water flow properties were measured in the falling jet and in the plunging pool using an intrusive phase-detection probe, with jet impact velocities between 2.5 m/s and 7.4 m/s and a fixed jet length. The falling jet was characterised by large disturbance and substantial pre-aeration. Intense air-water mixing was observed downstream of the impingement point. The development of air diffusion layer and turbulent shear layer was characterised by the streamwise evolution of void fraction, bubble count rate, bubble chord length and interfacial velocity profiles. The results compared favourably with the literature, albeit some difference was observed associated with different inflow jet turbulence levels as well as instrumentation development and signal processing refinement, including instrumental size, scanning rate and duration. The clustering properties were derived using the near-wake criterion. Results were comparable to those in horizontal hydraulic jumps. The air-entrainment rate was derived, highlighting the significant contribution of jet pre-aeration.